Induction of metastatic potential by TrkB via activation of IL6/JAK2/STAT3 and PI3K/AKT signaling in breast cancer - Kim, Min Soo (Oncotarget, 2015)
In metastatic breast cancers, the acquisition of metastatic ability, which leads to clinically incurable disease and poor survival, has been associated with acquisition of epithelial-mesenchymal transition (EMT) program and self-renewing trait (CSCs) via activation of PI3K/AKT and IL6/JAK2/STAT3 signaling pathways. We found that TrkB is a key regulator of PI3K/AKT and JAK/STAT signal pathway-mediated tumor metastasis and EMT program. Here, we demonstrated that TrkB activates AKT by directly binding to c-Src, leading to increased proliferation. Also, TrkB increases Twist-1 and Twist-2 expression through activation of JAK2/STAT3 by inducing c-Src-JAK2 complex formation. Furthermore, TrkB in the absence of c-Src binds directly to JAK2 and inhibits SOCS3-mediated JAK2 degradation, resulting in increased total JAK2 and STAT3 levels, which subsequently leads to JAK2/STAT3 activation and Twist-1 upregulation. Additionally, activation of the JAK2/STAT3 pathway via induction of IL-6 secretion by TrkB enables induction of activation of the EMT program via induction of STAT3 nuclear translocation. These observations suggest that TrkB is a promising target for future intervention strategies to prevent tumor metastasis, EMT program and self-renewing trait in breast cancer.